1998
DOI: 10.1590/s0004-282x1998000400011
|View full text |Cite
|
Sign up to set email alerts
|

Paralisia do nervo ulnar na lepra sem alterações cutâneas: biópsia do ramo superficial do nervo ulnar na mão

Abstract: RESUMO -A lepra constitui causa frequente de acometimento de nervos periféricos, em nosso meio. O sistema nervoso periférico é acometido por vezes sem que haja alterações cutâneas: é a chamada forma neurítica pura. Nessa variante, o nervo mais afetado é o ulnar. Nos casos de acometimento isolado de nervos periféricos somente a feitura de biópsia de nervo conduzirá ao diagnóstico. Assim, resolvemos realizar biópsia do ramo sensitivo superficial do nervo ulnar na mão em 17 pacientes com paresia ou paralisia dess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…Mononeuritis is the most common presentation of the neuritic form of leprosy and the ulnar nerve is the most affected. We had shown that in these cases the biopsy of the superficial ulnar nerve in the hand is the best way to diagnose leprosy 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Mononeuritis is the most common presentation of the neuritic form of leprosy and the ulnar nerve is the most affected. We had shown that in these cases the biopsy of the superficial ulnar nerve in the hand is the best way to diagnose leprosy 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The DCBU has been suggested as a site of biopsy for diagnostic purposes ( Chimelli et al, 1997 ; Freitas et al, 1998 ) , particularly in cases under investigation for a leprosy neuropathy. This study aims at describing DCBU microscopic aspects and the histometric parameters of its myelinated and unmyelinated fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Pure neuritic leprosy is a subtype of leprosy that represents up to 8% of all leprosy cases [9]. Nerve biopsy is the diagnostic gold standard, with a reported sensitivity of 33.3-75.9% of cases [36][37][38]. Pure neuritic leprosy presents as an isolated peripheral neuropathy.…”
Section: Neuritic Leprosymentioning
confidence: 99%